Thrombin dynamics in children with liver disease or extrahepatic portal vein obstruction or shunt. Issue 188 (April 2020) - Beattie, William; Kremers, Romy; Magnusson, Maria; Peters, Tessa; de Laat, Bas; Hardikar, Winita; Monagle, Paul; Ignjatovic, Vera
Abstract: Introduction: Changes in the coagulation profile in children with liver disease and extrahepatic portal vein obstruction or shunt result in both bleeding and thrombosis. Routine coagulation tests do not accurately predict bleeding risk, as they are not sensitive to changes in anticoagulant factors. The thrombin generation assay could be suitable for describing the overall balance of coagulation in children with liver disease. This study aims to characterise the mechanism of thrombin generation in this population, focusing on prothrombin conversion and thrombin inhibition. Methods: Patients were categorised as: severe (paediatric end stage liver disease score > 15) and mild disease, or portal vein obstruction or shunt. Age and gender matched healthy controls were used. The thrombin generation assay was performed in plasma samples from patients and controls with and without exogenous thrombomodulin and the results were further analysed with the computational thrombin dynamics method. Results: A total of 42 patients (severe, n  = 5; mild, n  = 29, obstruction/shunt, n  = 8) and 20 controls were included in this study. The total prothrombin conversion, thrombin-antithrombin formation and the thrombin decay capacity, in the presence and absence of thrombomodulin were reduced in children with severe liver disease. The rate of prothrombin conversion was increased and thrombin decay capacity was decreased in patients with portal vein obstruction or shunt compared to controls. Conclusion: This study demonstrates changes in the mechanism in thrombin generation seen in severe chronic liver disease. The changes vary in parenchymal versus non parenchymal liver disease and further study assessing the clinical significance of these variations in mechanism is required. Highlights: The thrombin generation assay represents an alternative to traditional coagulation tests in paediatric chronic liver disease. Children with liver disease have a reduction in both the rate of prothrombin conversion and thrombin decay capacity. In extrahepatic portal vein obstruction or shunt the balance of haemostatic changes tend towards a pro-thrombotic state.